FIGURE 1 in The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species ... - Garbin, Lucas E.; Diaz, Julia I.; Servián, Andrea; Fusaro, Bruno; Navone, Graciela T. (Zenodo, 2023)
FIGURE 1. Distribution of Neotropical and Antarctic Contracaecum species indicated by reference numbers according to Table 1. ... : Published as part of Garbin, Lucas E., Diaz, Julia I., Servián, Andrea, Fusaro, Bruno & Navone, Graciela T., 2023, The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species, pp. 43-62 in Zootaxa 5256 (1) on page 56, DOI: 10.11646/zootaxa.5256.1.3, http://zenodo.org/record/7745326 ...